Komunikasi Interpersonal dalam Membangun Relationship Antara Kepala Madrasah dengan Guru di MIN 5 Bandar Lampung - Devin Cumbuan Putri; Erjati Abas; Via Retno Monica (Journal on Education, 2024)
Communication is important and an activity that cannot be separated from an individual. With good communication, it will have a good impact so that the goals to be achieved can be easily achieved. Communication is essentially the process of conveying messages between people, both in groups and individually. Interpersonal communication is the process of exchanging information between one person and at least one other person. This research aims to describe interpersonal communication in building relationships between madrasa heads and teachers. The method used is a descriptive method with a qualitative approach. Research data collection was carried out through interviews, observation and documentation. The data sources used are primary data sources and secondary data sources. This research data analysis uses data reduction, data presentation and conclusion drawing, while data validity testing uses source triangulation. The results of the research show that the implementation of interpersonal communication in building relationships between madrasa heads and teachers at MIN 5 Bandar Lampung shows that: 1.) Openness of communication between madrasa heads (plt) and teachers has been running according to its portion. The head of the madrasah (plt) is open and open, listens and is transparent with information. On the other hand, teachers are also open. 2.) The empathetic attitude of the madrasa head (plt) is good with his willingness to listen and respond to the messages conveyed by the teacher. Apart from that, he continues to try to show empathy when the teacher is feeling down. 3.) Support in developing interpersonal communication is good and is carried out through providing professional guidance, encouraging teachers to get involved in activities and open up. 4.) Positive attitude, in the madrasa environment we are used to greeting each other when we meet. The head of the madrasah (plt) builds closeness by establishing kinship, giving praise and rewards, as well as giving advice 5.) In equality, the head of the madrasah (plt) always strives to avoid differences by giving everyone the right to freedom of opinion and being able to adapt to conditions.